Multi-Scale Integrated Analysis of Charcoal Production in Complex Social-Ecological Systems - González-López, Rafael; Giampietro, Mario (Frontiers in Environmental Science, 2017)
We propose and illustrate multi-scale integrated analysis of societal and ecosystem metabolism (MuSIASEM) as a tool to bring nexus thinking into practice. MuSIASEM studies the relations over the structural and functional components of social-ecological systems that determine the entanglement of water, energy and food flows in a complex metabolic pattern. MuSIASEM simultaneously considers various dimensions and multiple scales of analysis and therefore avoids the predicament of quantitative analysis based on reductionism (one dimension and one scale at the time). The different functional elements of society (the parts) are characterized using the concept of ‘processor’, that is, a profile of expected inputs and outputs associated with the expression of a specific function. The processors of the functional elements of the social-ecological system can be scaled-up to describe the metabolic pattern of the system as a whole, and scaled-down by considering the characteristics of its lower-level parts – i.e. the different processors associated with the structural elements required to express the specific function. An analysis of functional elements provides insight in the socio-economic factors that pose internal constraints on the development of the system. An analysis of structural elements makes it possible to study the compatibility of the system with external constraints (availability of natural resources and ecological services) in spatial terms. The usefulness of the approach is illustrated in relation to the use of charcoal in a rural village of Laos.